Content, language and intercultural challenges in engineering education: (E-)strategies to improve instructional design - Morgado, Margarida (2018)
Intercultural, multilingual and culturally and academically diverse classrooms are a common reality in current higher education (HE) landscapes, as globalisation is effectively taking place in all major schools. Rethinking instructional design strategies that contribute to the overcoming of communication and cultural differences in both online and blended learning processes may help not only improve the development of more efficient online learning environments but also meet the challenges of current teaching and learning processes. Special focus will be put into engineering education through the medium of English and the training of engineering lecturers in HE through communities of practice (CoPs), which present, integrate and discuss how to integrate content and language (through what is known as the content and language integrated learning (CLIL) approach) as well as trends, challenges and opportunities related to recent technological developments on students’ learning ourcomes. The desciption of the pedagogical training shared through a CoP describes E-strategies to improve instructional design in engineering courses in online learning environments when English is used as a medium of instruction and integrated with content in a CLIL approach.